2007
DOI: 10.21273/jashs.132.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity and Relationships Among Caladium Cultivars and Species Using Molecular Markers

Abstract: Caladium (Caladium ×hortulanum Birdsey) is an important aroid widely used in the ornamental plant industry. Concerns have been raised about possible loss of genetic diversity due to a drastic decline in the number of cultivars in the last century. This study assessed genetic diversity and relationships among caladium cultivars and species accessions. Forty-five major cultivars and 14 species accessions were analyzed based on 297 DNA fragments produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…A significant difference in disease severity was observed between the two caladium cultivars in controlled environments, suggesting that there may be varying levels of resistance to S. sclerotiorum within cultivars of caladium. The pedigrees of many cultivars of Caladium ·hortulanum are unknown, but most are believed to originate from C. bicolor, C. picturatum, C. marmoratum, or C. schomburgkii (Deng et al, 2007). Future studies could be conducted to identify resistance in other caladium cultivars or species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant difference in disease severity was observed between the two caladium cultivars in controlled environments, suggesting that there may be varying levels of resistance to S. sclerotiorum within cultivars of caladium. The pedigrees of many cultivars of Caladium ·hortulanum are unknown, but most are believed to originate from C. bicolor, C. picturatum, C. marmoratum, or C. schomburgkii (Deng et al, 2007). Future studies could be conducted to identify resistance in other caladium cultivars or species.…”
Section: Discussionmentioning
confidence: 99%
“…Caladium originates from tropical regions of Central and South America (Germplasm Resources Information Network, 2017). Breeding of hybrid garden caladium has occurred for over 150 years (Deng et al, 2007). Elephant ear, also known as taro, originates from Southeast Asia and is believed to be one of the oldest domesticated crops (Quero-Garcia et al, 2010).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that TRAP markers are suitable for assessing genetic diversity in different crops and plants (Hu et al, 2005; Alwala et al, 2006; Deng et al, 2007; Hu et al, 2007). Results in this study also suggested that TRAP markers can be used for genetic diversity studies in sunflower.…”
Section: Discussionmentioning
confidence: 99%
“…The TRAP marker technique utilizes a fixed primer designed against a known sequence in combination with two arbitrary primers to generate polymorphic markers (Hu and Vick, 2003). Since it is easy to perform and allows for relatively high throughput, the TRAP technique has been successfully applied to the studies of sunflower genome mapping (Hu, 2006) as well as germplasm diversity and population genetics in other plant species, including spinach ( Spinacia oleracea L.) (Hu et al, 2007), lettuce ( Lactuca sativa L.) (Simko and Hu, 2008), sugarcane (Alwala et al, 2006), and a Caladium germplasm collection (Deng et al, 2007).…”
mentioning
confidence: 99%
“…Jaccard's similarity coefficient for ISSR data also indicated a moderate level of similarity coefficient between C-2016 and M. multicaulis (0.53), Shrim-5 (0.54), and Kenmochi (0.55). A higher similarity coefficient indicates genetic closeness of the genotypes (Deng, Goktepe, and Harbaugh 2007). Therefore, the identified mulberry genotypes with low similarity coefficients can be utilized in controlled crossing programs.…”
Section: Effectiveness Of Dna Markersmentioning
confidence: 99%